Nutritional Value Evaluation and Processing Technology of Feed and Nutrition Regulation Measures for Ruminants - Dingfu Xiao; Tiantian Meng (Animals)
In the context of modern livestock farming, particularly in the ruminant industry, feed is a crucial factor that affects both the efficiency of production and animal health [...]